Bovine adipose mitochondrial adaptation and a potential lactate–ketone toggle in early lactation - O’Boyle, Nial J.; Chirivi, Miguel; Abou-Rjeileh, Ursula; Salcedo-Tacuma, David; dos Santos Neto, José M.; Prom, Crystal; Parales-Girón, Jair; Lock, Adam L.; Stöger, Reinhard; Chakrabarti, Lisa; Contreras, G. Andres (Frontiers in Veterinary Science, 2025)
The periparturient period creates an intense energy demand due to the onset of lactation, which requires substantial glucose for milk synthesis, particularly in high producing cows, contributing to a high incidence of postpartum metabolic disease. We explored the transcriptomic adaptation of subcutaneous adipose tissue (AT), with a specific focus on metabolic gene networks and the mitochondrial component. Mitochondria coordinate cellular energy dynamics by linking the oxidation of nutrients to ATP synthesis via oxidative phosphorylation (OXPHOS). However, their role in postpartum metabolic disease is not clear. We therefore re-analysed a longitudinal RNA-seq dataset of subcutaneous AT from 12 healthy multiparous Holstein cows, sampled pre-calving and at two early-lactation time-points, to explore mitochondrial pathways. This analysis revealed downregulation of differentially expressed genes (DEGs), encoding components of the electron transport system and OXPHOS, in the postpartum phase, concurrent with a shift to DEGs associated with glycolysis. Given the observed glycolytic shift, an analysis of plasma lactate during the periparturient period was undertaken, to explore how this glycolysis-derived substrate fluctuates in this altered metabolic state. A postpartum decline in plasma lactate, alongside rising β-hydroxybutyrate, was further demonstrated in clinical ketotic cows, revealing a potential metabolic toggle between lactate and ketones; aligning with the concept that fuel sources will alter depending on redox and metabolic conditions. This supports the emerging view that ketones are not merely pathological markers but may serve as adaptive metabolic signals, warranting further investigation into their role in dairy cow metabolism. Further understanding of how mitochondria function during this energy-intensive postpartum phase of the dairy cow, may help elucidate how adipose tissue contributes to metabolic resilience or perturbation during early lactation.